2002
DOI: 10.1161/01.str.0000016972.70366.d6
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution, Contrast-Enhanced Magnetic Resonance Angiography With Elliptical Centric k-Space Ordering of Supra-aortic Arteries Compared With Selective X-Ray Angiography

Abstract: Background and Purpose-The objective of this study was to evaluate the relative value of high-resolution, contrastenhanced MR angiography (CE MRA) with elliptical centric k-space ordering compared with intra-arterial x-ray angiography for imaging carotid stenosis. Methods-Thirty patients with suspected stenosis of the carotid arteries were examined with CE MRA (1.5-T scanner) and x-ray angiography (aortic arch survey and selective imaging of both common carotid arteries). For the first time, not only the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 26 publications
3
46
1
4
Order By: Relevance
“…Of these papers, 37 TOF MRA 17,18,26 -60 and 21 CE MRA papers 16,26,27,33,35,37,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] fulfilled the inclusion criteria (Tables 1 and 2). Of the TOF papers, 11 used 2D TOF MRA, 14 used 3D TOF MRA, and 12 included both 2D and 3D TOF data (Table 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…Of these papers, 37 TOF MRA 17,18,26 -60 and 21 CE MRA papers 16,26,27,33,35,37,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] fulfilled the inclusion criteria (Tables 1 and 2). Of the TOF papers, 11 used 2D TOF MRA, 14 used 3D TOF MRA, and 12 included both 2D and 3D TOF data (Table 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…It has been shown that 3D TOF angiography produces superior quality of carotid arteriograms as compared to 2D TOF or phase-contrast sequences (45). Ultrafast 3D gradient-echo sequences with elliptic-centric phase encoding represent the method of choice for acquisition in the first-pass contrast-enhanced MRA (46,47). For black blood imaging, the 3D approach can potentially provide important benefits, such as a reduction of slice thickness and an increased SNR.…”
Section: Imaging Pulse Sequencesmentioning
confidence: 99%
“…Moreover, TOF-MRA is usually acquired through the carotid bifurcation only and with a higher spatial resolution, as CE-MRA is typically optimized for coverage from the aortic arch to the skull base, and this may enhance the ability of TOF-MRA to detect small ulcers. Despite these merits, TOF-MRA is often inadequate for detecting tandem lesions 15,16,18 and is prone to saturation of slowly flowing or recirculating blood protons, resulting in signal loss within a severely compromised lumen or the carotid bulb, respectively. 19,20 Recirculating blood proton saturation could also affect the signal within an ulcer crater.…”
mentioning
confidence: 99%